Nitric oxide donor 8-bromo-cGMP suppresses cholesterol depleted RBCs band 3 dysfunction : 8-bromo-cGMP suppresses cholesterol depleted RBCs band 3 dysfunction - Vijayaraghavan, Mahalakshmi; Sengupta, Prattusha; Chatterjee, Suvro; Jayavelu, Tamilselvan (Cellular and Molecular Biology, 2022)
Red blood cells (RBCs) carry large cholesterol fractions and imbalance in them leads to several vascular complications. RBCs band 3 protein plays an important role in maintaining membrane integrity and there are many reports on cholesterol and band 3 protein interaction. Yet, RBCs band 3 protein role in regulating cholesterol homeostasis needs to be investigated. In this study, we induced cholesterol-depletion and band 3 inhibition in RBCs; both of which cause stress by decreasing band 3 channel activity with an increase in RBCs adhesion to endothelial cells (EC) by elevating band 3 phosphorylation (Tyr21), methemoglobin level and decreasing nitric oxide level. We hypothesized that nitric oxide (NO), a prominent determinant for RBC structural stability, would protect RBCs from stressors. To estimate this, we used three NO donors (SpNO, Sildenafil citrate and 8-Bromo-cGMP) and found that all 3 NO donors were able to recover, with 8-Bromo-cGMP being the most effective as it not only increased band 3 channel activity but also decreased RBC-EC adhesiveness and methemoglobin level in both stressors. Whereas NO donor’s treatment did not display an ameliorative impact when both stresses were combined. Overall, these findings may shed light on the role of 8-bromo-cGMP in regulating RBC cholesterol homeostasis by maintaining band 3 function. Further studies in this direction might help identify targets for the therapeutic use of NO donors in the treatment of blood disorders.